OPTIMALISASI PERLINDUNGAN HAK ATAS KENYAMANAN WISATAWAN DI KAWASAN WISATA KOTA MATARAM - I Gusti Agung Wisudawan; Budi Sutrisno; Ari Rahmad Hakim BF; Diman Ade Mulada (Journal of Innovation Research and Knowledge, 2024)
Tourism is an inseparable part of the national development of the Indonesian nation. To manage tourism, of course, human resources, adequate facilities and infrastructure and integrated management are needed. This research will describe the form of protecting the personal rights of tourists' comfort in the Mataram City Tourist Area and the Legal Responsibilities of Tourism Service Companies and the Mataram City Regional Government in guaranteeing the personal rights of tourists' comfort in the Tourist Area as well as providing appropriate policy formulations for tourism legal subjects in order to ensure business sustainability. tourism in Mataram City. The research method used is a normative research method with a statute approach and a conceptual approach. The technique for collecting legal materials is carried out using Document Study and Qualitative Analysis of Legal Materials, that is, library legal materials are analyzed in depth, holistically and comprehensively and the conclusions drawn are carried out deductively. The results of this research are that protecting the rights to personal comfort of tourists in tourist areas in Mataram City includes preventive protection, namely that the Mataram City Tourism Office must carry out regular outreach to the community around tourist destinations about tourist safety and comfort, opening up opportunities for local residents to participate in business. and maintaining the area around the destination and providing adequate facilities and infrastructure for tourists. Repressive legal protection is that the Mataram City Tourism Office must collaborate with law enforcement officials, especially the Mataram City Sector Police and mass organizations in the context of taking action and protecting tourists. The responsibilities of tourism business actors towards tourists as consumers who use services are regulated in Article 19 of Law No. 8 of 1999 concerning Consumer Protection and Articles 26 d and e as well as Article 63 of Law Number 10 of 2009 concerning Tourism. The government's responsibility to guarantee the protection of tourists' personal rights to comfort has actually been regulated in Law Number 10 of 2009 concerning Tourism in terms of making policies as regulated in Articles 28, 29 and 30.